Combination therapy for the treatment of pancreatic cancer through hyaluronic acid‐decorated nanoparticles loaded with quercetin and gemcitabine: A preliminary in vitro study. Issue 4 (18th October 2018) - Serri, Carla; Quagliariello, Vincenzo; Iaffaioli, Rosario Vincenzo; Fusco, Sabato; Botti, Gerardo; Mayol, Laura; Biondi, Marco
Abstract: Combination chemotherapy by means of two or more drugs is prone to suppressing or discouraging the inception of multidrug resistance, exploiting the fact that diverse drugs act in different points of the cellular cycle of amplifying tumor cells. For example, the combination of gemcitabine (GMC) with quercetin (QCT) showed a synergistic effect in inhibiting the migration of pancreatic cancer cells. Consequently, herein GMC and QCT have been loaded within biodegradable nanoparticles (NPs) based on poly(lactic‐co‐glycolic acid), externally decorated with hyaluronic acid (HA; viz., PPHA NPs), which plays a major role in drug targeting to tumors due to its ability to specifically interact with CD44 receptor, that is overexpressed in many tumors. The produced HA‐decorated NPs loaded with GMC and QCT showed an improved cytotoxicity and cellular uptake toward two cell lines of pancreatic ductal adenocarcinoma, namely Mia‐PaCa‐2 and PANC‐1, compared with both the bare drugs and the drugs loaded in NPs which do not expose HA on the surface. HA‐decorated NPs were also able to improve the anti‐inflammatory properties of QCT, therefore leading to a decrease of interleukin cellular levels in both cell lines, preliminarily stimulated with lipopolysaccharides. This result is of special interest also considering the crucial role of interleukins in progression, metastatic processes, and drug resistance of human pancreas cancer cells. Abstract : Gemcitabine (GMC) and quercetin (QCT) have been loaded within biodegradable nanoparticles (NPs) based on poly(lactic‐co‐glycolic acid), externally decorated with hyaluronic acid (HA). The produced HA‐decorated NPs loaded with GMC and QCT showed an improved cytotoxicity and cellular uptake toward both Mia‐PaCa‐2 and PANC‐1, compared with both the bare drugs and the drugs loaded in NPs which do not expose HA on the surface. HA‐decorated NPs were also able to improve the anti‐inflammatory properties of QCT, therefore leading to a decrease of interleukin cellular levels in both cell lines, preliminarily stimulated with lipopolysaccharides.